Mapping existing hip and knee replacement registries in Europe. Issue 5 (May 2018) - Lübbeke, A.; Silman, A.J.; Barea, C.; Prieto-Alhambra, D.; Carr, A.J.
Highlights: Registries are a major resource for high-quality medical device data. There are 24 arthroplasty registries in Europe, most of national coverage. 3.1 million hip and 2.5 million knee arthroplasties are registered since 1975. Focus is on long-term implant surveillance, benchmarking, and quality assessment. Depth of data regarding baseline characteristics and outcomes has progressively increased. Abstract: The general shortage of evidence regarding benefits and harms of medical devices has been highlighted following the serious safety concerns with metal-on-metal hip replacements and silicone breast implants and was again pointed out in a recent survey of European Health Technology Assessment institutions. In this context the new European medical device regulation will enforce post-marketing surveillance of existing and new implants. The usefulness of registry data as a source of information for medical device real-world clinical performance and safety has been demonstrated. However, these data might be under-used by researchers and policy makers. One reason for this is the insufficient awareness of their existence. The aim of this review is to provide information to relevant stakeholders on the extent and breadth of the data currently collected in European joint replacement registries. We identified 24 registries, most of them of national coverage. Total numbers of primary total hip and knee replacements included were over 3.1 and 2.5 million records, respectively. The current focus of these registries is on whole-lifespan implant surveillance via revision rate monitoring, quality assessment of surgical and perioperative care, and hospital performance assessment. More recently, national and international comparison and benchmarking have increasingly become part of their endeavors.